The further adventures of Robinson Crusoe - Defoe, Daniel 1660-1731 (Project Gutenberg, 1990)
As part of ClassicReader.com, Stephane Theroux presents the full text of "The Further Adventures of Robinson Crusoe," by English novelist Daniel Defoe (1660-1731). Defoe is often considered the founder of the English novel.